The role of geospatial technologies in football: National football recruiting / Muhammad Haziq Hafizi Hafnizam and Adib Hakimi Mohamad Rosly - Hafnizam, Muhammad Haziq Hafizi; Mohamad Rosly, Adib Hakimi (Universiti Teknologi MARA (UiTM), 2024)
National football recruiting is an initiative that uses a Geographic Information System (GIS) to manage the recruitment process. This effort focuses on acquiring young players under the age of 21 from four countries: Spain, France, Germany, and England. This initiative was undertaken because many football clubs do not incorporate logistical planning into their recruitment processes. This creates several elements that cannot be discovered during the hiring process, which can bring convenience and prevent future problems. Using GIS in the recruitment process, elements such as distance and time can be detected to assist the football club's coach and staff in selecting the best player to recruit. The player data used in this project includes the academy player's name, age, and coordinates.